Medication disposal: practices and knowledge of its impacts to the environment among the community pharmacy customers / Shaharuddin Abdul Rashid - Abdul Rashid, Shaharuddin (2014)
Background: The usage of medication is increasing in Malaysia. The amount of medication being thrown away as trash is huge every year. The metabolites of each medication also being flushed down the sewage system every day. The purpose of this study is to know the disposal method of unwanted medication and the knowledge of its impacts to the environment. The study participants were the customers of the community pharmacy. Methodology: This is a cross sectional study involving community pharmacy customers in Shah Alam Municipality, Selangor. Data was collected from April to Mei 2014' Result: A pilot study demonstrated that the questionnaire was valid and reliable to assess the customers practice and knowledge toward medication disposal. The most utilized disposal method was to dispose as thrash either in the bottle or strip or pour out the medication from their respective containers into the trash. The customers did not agree with the statement that medication residue can harm the environment. Conclusion: These findings showed that community pharmacy customer's medication disposal preferred method is to dispose them as trash and they did not know about the impacts of medication residue to the environment. Therefore, it is recommended that better regulations are required to ensure that the disposal of unwanted medication will no longer cause harmful impacts to the environment. The community pharmacist also need to play proactive roles in educating their customers about the harmful impacts of improper medication disposal to the environment. Keywords: Medication disposal, community pharmacy customers, knowledge, harmful impacts, environment